2021
DOI: 10.3390/ijms22041744
|View full text |Cite
|
Sign up to set email alerts
|

Time-Course Changes of Extracellular Matrix Encoding Genes Expression Level in the Spinal Cord Following Contusion Injury—A Data-Driven Approach

Abstract: The involvement of the extracellular matrix (ECM) in lesion evolution and functional outcome is well recognized in spinal cord injury. Most attention has been dedicated to the “core” area of the lesion and scar formation, while only scattered reports consider ECM modification based on the temporal evolution and the segments adjacent to the lesion. In this study, we investigated the expression profile of 100 genes encoding for ECM proteins at 1, 8 and 45 days post-injury, in the spinal cord segments rostral and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
(78 reference statements)
1
4
0
Order By: Relevance
“…At 45 DPL, same genes are differentially expressed rostrally and caudally to SCI site. In particular, only Timp1 remains up-regulated, as previously described [30], and Nr4a1 down-regulated in both segments; while Egr3 and Gnai1 are downregulated in the rostral and caudal segment, respectively. The different gene members of the EGR family of transcriptional regulators are involved in CNS function, and Egr3 is required specifically for short-term memory [34].…”
Section: Discussionsupporting
confidence: 79%
“…At 45 DPL, same genes are differentially expressed rostrally and caudally to SCI site. In particular, only Timp1 remains up-regulated, as previously described [30], and Nr4a1 down-regulated in both segments; while Egr3 and Gnai1 are downregulated in the rostral and caudal segment, respectively. The different gene members of the EGR family of transcriptional regulators are involved in CNS function, and Egr3 is required specifically for short-term memory [34].…”
Section: Discussionsupporting
confidence: 79%
“…62 The cell response is the basic unit in the pathophysiology of SCI and has temporal and spatial characteristics. 33,63 The elucidation of the cellular response, especially the response mechanisms of different cell subsets, is of great significance for finding effective intervention targets for SCI. The pathological mechanism of SCI discussed in this review mainly focuses on rodents.…”
Section: Overall Incidence and Demographic Characteristicsmentioning
confidence: 99%
“…To demonstrate the effect of SynCAM3 deletion, we evaluated the relationship between SynCAM3 and gene expression in the injured cord. The heat map visually showed dynamic changes in the expression of all genes at 2, 4, 7, and 14 DPI ( Figure 1 C) [ 34 , 35 ]. It was confirmed that the most genetic changes occurred at seven DPI, when the expression of SynCAM3 was the lowest after SCI.…”
Section: Resultsmentioning
confidence: 99%